Factors influencing affective organizational commitment among primary school leaders in Kuching, Sarawak / Sharkawi Annuar - Annuar, Sharkawi (2012)
The purpose of this study is to identify the factors influencing the affective organizational commitment among the school leaders’ in Kuching, Sarawak. The research sample were 189 school leaders from the government primary schools in kuching. They are the headmasters, senior assistances and subject panel heads. This survey used a self directing instrument in form of questionnaires. The result shows that there is a strong, positive and significant relationship between leadership style, knowledge sharing, employee relationship, task orientation, compensation and incentives, performance management and promotion opportunities and training and development in effective organizational commitment of the primary school leaders in Kuching. Thus, Null Hypothesis no. 1 - 7 was rejected, whereas for null hypothesis no. 8-9, we fail to reject the null hypothesis. There is no differences affective commitment among the male and female school leaders. There is also no differences in affective commitment among school leaders who teachers in school of differences location. Thus, the findings of this research are significantly important for interested parties in the field of affective organizational commitment among the school leaders and some suggestions are also raised for further researches to better understanding of the affective organizational commitment among school leadership future.